From Policy to Practice: How Indonesian Universities’ Syllabi and LMS Materials Address ChatGPT in EFL Writing Instruction - Rohmah, Farida Noor (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study examines how Indonesian universities incorporate ChatGPT and other artificial intelligence (AI) techniques in English as a Foreign Language (EFL) writing teaching via institutional documents.Method – A qualitative document analysis was conducted on three syllabi and one set of Learning Management System (LMS) materials collected from three Indonesian universities between March and May 2025. Findings – The results indicate that while all syllabi addressed originality through similarity thresholds, only one out of three (33%) explicitly mentioned AI, and none provided instructional guidance on its responsible use. Two universities (67%) set specific Turnitin similarity limits, whereas none included learning activities or materials that integrated AI literacy. LMS materials primarily restated these evaluative criteria without incorporating further pedagogical support. Research Implications – The paper offers a curricular viewpoint on current discussions over AI integration in higher education and advocates for more explicit, pedagogically grounded policies that reconcile academic integrity with the enhancement of AI literacy in EFL writing teaching. As practical guidance, institutions could (1) incorporate a syllabus clause specifying permitted AI supports, with mandatory disclosure and attribution statements, and (2) develop an LMS checklist that links to AI literacy micro-modules, fact-checking worksheets for AI-generated content, and reflective prompts on ethical use.